"WhatsApp"ening in mission hospitals: An essential mobile health tool for young fresh graduates - Nirmal Kurian; Deeptiman James; Vinaya Susan Varghese (Wolters Kluwer Medknow Publications, 2018)
The dawn of mobile health facilitates new horizon of professional communication through WhatsApp, allowing health professionals to interact quickly and efficiently for effective patient management. Dedicated group chats can bring together novices and experts of medical and dental specialties in a common platform. This article highlights how the use of WhatsApp services help improve communication and coordination among the young graduates in remote mission hospitals and senior specialists in WhatsApp group, thereby helping in delivering superior treatment plans to underprivileged people in remote parts of India.